The Survival Power Weibull Distribution With Application - Kalt, Hazim; Abdul Sada, Majida T. (Statistics, Optimization & Information Computing, 2025)
The primary objective of this research is to investigate a novel lifetime distribution characterized by three parameters, which is constructed through the amalgamation of the Weibull distribution and the Survival Powe-G family. The recently introduced model is referred to as the SPW distribution. The newly formulated distribution possesses the advantage of effectively modeling various data types, thus proving to be instrumental in the domains of reliability and lifespan statistics. Several statistical properties pertinent to the SPW distribution are examined in this study. The recommended estimation approach is the maximum likelihood method. Empirical tests of the SPW distribution are presented by using two real datasets. Furthermore, SPW distribution demonstrates a good fit, backed by comparisons with Weibull-based models and other alternative distributions using several goodness-of-fit assessments.